PENERAPAN SISTEM MANAJEMEN MUTU MELALUI ANALISIS SWOT UNTUK MENINGKATKAN KUALITAS PEMASARAN PRODUK - Telaumbanua, Faudunasokhi; ono, Supry (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
This research aims to determine the implementation of a quality management system and to determine the quality of product marketing through SWOT analysis. Product marketing quality is focused on commodities on a small scale, to implement a quality management system that can be measured efficiently. SWOT analysis is used to interpret several approaches that can contribute to improving the quality of product marketing. Researchers carried out probability sampling using a purposive sampling technique. The sample is the market around Alwasliyah University. The research approach was carried out quantitatively and qualitatively by applying action research methods. The research results show that the implementation of a quality management system has an average contribution value of 77.75 through SWOT analysis to improve product marketing quality. There are 3 of 8 product marketing criteria that cause the implementation of a quality management system in turn around conditions. So this research recommends that there is a need to exploit opportunities to optimize product marketing.